A Statistical Analysis of Post Burn Flexion Deformities in Kashmir - C. N. Malla; Nancy Malla; B. M. Bhan (Indian Journal of Plastic Surgery)
A statistical analysis of post burn constractures was made with a view to find out the etiology and mechanism of post burn contractures.